If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(1 + 2k) = -6 + -4k (1 * -6 + 2k * -6) = -6 + -4k (-6 + -12k) = -6 + -4k Add '6' to each side of the equation. -6 + 6 + -12k = -6 + 6 + -4k Combine like terms: -6 + 6 = 0 0 + -12k = -6 + 6 + -4k -12k = -6 + 6 + -4k Combine like terms: -6 + 6 = 0 -12k = 0 + -4k -12k = -4k Solving -12k = -4k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '4k' to each side of the equation. -12k + 4k = -4k + 4k Combine like terms: -12k + 4k = -8k -8k = -4k + 4k Combine like terms: -4k + 4k = 0 -8k = 0 Divide each side by '-8'. k = 0 Simplifying k = 0
| 2(4+20-1)= | | n+.6=n | | -3(2X-1)+5=50 | | 1+8n+5=-2 | | (3)(2)(-30)= | | 10x-3=5x+10 | | -14x+5y=19 | | 4(b-6)=71-2b | | 15+18-12=x | | 10p(1+9p)=8p^2 | | .667x+5=4 | | 8+20(3x+1)= | | 12x-8=8x-28 | | 2x-27-10=16 | | 4+x+3= | | x*5x=20 | | 2m+5=5m-7-5m | | -10x+2=10 | | 4x^2+10x=x+8 | | -10(-v+3)+6(v-11)=v+3+6 | | 54=4x^2-2X-2 | | (6x+2)=(5x+7) | | b*5a=20 | | 3(x+1)=5x-6 | | 4x+7=2-(8x-8) | | 2x+4y+6y-3xy=0 | | 5t+(2t-1)+t=27 | | 26+12-18=x | | 3x(x^2+9)=0 | | pie=7x+2y | | -6w+2=-28 | | -8(a-10)=-8(a-1)+2 |